Retooling the Mind Factory: Education in a Lean State - Sears, Alan (Garamond Press, 2003)
Alan Sears examines education reform in relation to a broad process of cultural and economic change. His book makes the case that education reform is one aspect of a broad-ranging neo-liberal agenda that aims to push the market deeper into every aspect of our lives by eliminating or shrinking non-market alternatives. The author begins by showing that advocates of education reform have had to make the case that the current system is not working. This sets the ground for an examination of the so-called 'Common Sense Revolution,' a claim that drastic change was required to redesign government policies to fit a changing world. Lean production methods are a crucial component of this changing world, and broader social and cultural change is now required to consolidate the emerging order built on the spread of these methods. Education reform is designed to recast the relations of citizenship, contributing to the cultural and social change promoted through the social policy of the lean state. --Publisher's description
Keywords: Conservatism; EDUCATIONAL change; Economic aspects; Education; Education and state; Ontario